Representasi Women Power Pada Film Karya Disney Studi Semiotika pada Film Mulan - Muhammad Abdurrauf Nasrullah; Alief Budiyono (Lembaga Pengembangan Kinerja Dosen, 2024)
This study focuses on how the portrayal of female power in one of Disney's films, Mulan. Film can provide a construct in socio-cultural reality. With this construction, the content of the film needs to be considered, because the content of the film can change the mindset of the audience who watches. Women are usually often complementary figures and do not have dominance than men. This is an interesting study because women can be constructed with the image above. Therefore, researchers dissect the portrayal of female power presented by Disney. Researchers use Ferdinand De Sausure's semiotic analysis method which focuses on signifiers and signified in interpreting women's power in Mulan. The supporting theory in this study is film as mass communication and women in the media. The results of the study showed three depictions of female strength from the film Mulan, namely women who are brave, women who resist and women who has a confident nature.